(untitled) (Marketing Journal, 2025)
The practical application of project management requires the use of specific methods. In construction production, project management plays a crucial role, as organizing construction processes involves ensuring the alignment of deadlines, quality, and cost—an inherently complex task. This article explores widely used project management approaches and outlines their characteristics.